The Influence of Beauty Vlog on Perceived Source Credibility and Purchase Intention - Rahmi, Yaumul; Sekarasih, Laras; Sjabadhyni, Bertina (Makara Human Behavior Studies in Asia, 2017)
This study examined the influence of beauty vlog on consumers’ purchase intention through consumers’ perceptions of source credibility and expertise, with consumers’ previous experience in using the product as a moderator. An experiments was conducted by exposing participants (n = 98) to a beauty vlog clip and a traditional advertising as a source of information on YouTube platform. Wardah lip cream products were used as a product in experiments. The results showed that the source of information had no effect on purchasing intention or consumer perception on the credibility and expertise of information sources. However, an interaction between information source and previous experience in using the product in influencing consumers’ purchase intention was found. Specifically, compared to traditional advertising, beauty vlog had a positive effect on the intention of purchase among individuals who had had used Wardah lip cream products.